Accounting and the management of power: Napoleon's occupation of the commune of Ferrara (1796–1799). (January 2016) - Maran, Laura; Bracci, Enrico; Funnell, Warwick
Highlights: Identification of the relationships between rationales or programs of government and technologies of government, most especially accounting, during the emergence of the modern State in the 18th century in northern Italy. Identification of two levels of political discourse (high and operational) during the Napoleonic occupation of the Commune of Ferrara, Italy. Extensive use of primary archival data to examine the scope and organisation of Napoleonic public administration and the 'governmentality' principles. Abstract: This study, which is informed by Foucault's concept of governmentality, identifies the systematic ties between political discourse, forms of rationality and technologies of government during the first period that Napoleon governed Ferrara in northern Italy (1796–99). The study identifies a decoupling between 'political discourses, rhetoric and language' and the use of 'technologies of government'. The results enhance understanding of the translation of politics and power into a set of administrative tasks and calculative practices to secure power in modern public sector settings today. In the neo-liberal prescriptions for the modern State which demand a much diminished role and presence for the government in the lives of its citizens, societies, organizations and their management are tending to be more and more concerned with surveillance made operable through power.